Pengaruh Kualitas Produk dan Promosi Penjualan Terhadap Keputusan Pembelian pada Nurza Brownies - Ardini, Sarah Fadhilla; Lubis, Nurul Wardani; Sherlinda, Azzahra; Tofano, Dwi Fatmi Adelina (Ikatan Da'i Indonesia, 2024)
This study aims to determine the effect of product quality and sales promotion on consumer purchasing decisions at Nurza Brownies Store in Medan. The number of samples taken in this study were 50 consumers. The data collection method in this study used a questionnaire to 50 consumers of the Nurza Brownies shop in Medan. The data analysis method used is the Validity, Reliability and Multiple Linear Regression method. The results of the partial test analysis show that product quality and sales promotion have a significant effect on consumer purchasing decisions. Furthermore, the results of simultaneous testing show that the variables of product quality and sales promotion have a significant effect on consumer purchasing decisions. The Adjusted R Square value is 0.771 or 77.1%. This means that 77.1% of consumer purchasing decisions are influenced by the two independent variables, while the remaining 22.9% of decisions are influenced by other variables not examined in this study.